2018
DOI: 10.2217/fon-2017-0678
|View full text |Cite
|
Sign up to set email alerts
|

SEER Study of Ablation Versus Partial Nephrectomy in cT1A Renal Cell Carcinoma

Abstract: Ablation offers similar CSS but lower OS as PN for T1A RCC in this SEER database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Conversely, some studies reported clinical outcomes to 5 years. Overall survival after IGTA of T1a RCC ranges from 74% to 97.8% with a weighted mean of 79% (15,17,18,22,23,68,69,77). The threshold for OS of IGTA for T1a RCC is 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies reported clinical outcomes to 5 years. Overall survival after IGTA of T1a RCC ranges from 74% to 97.8% with a weighted mean of 79% (15,17,18,22,23,68,69,77). The threshold for OS of IGTA for T1a RCC is 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding LTA versus nephrectomy originating from 7 institutional studies (from 1998 to 2012) formed the basis of a recent meta-analysis 7 , which showed a 3.4-fold increase of cancer specific mortality (CSM) when LTA was performed instead of partial (PN) or radical nephrectomy (RN). Conversely, of five population based studies [8][9][10][11][12] , only one 9 showed worse CSM for LTA relative to PN. However, their historic nature represents a limitation; the most recent included patients diagnosed from 2004 to 2013 12 .…”
Section: Introductionmentioning
confidence: 86%
“…Conversely, of five population based studies [8][9][10][11][12] , only one 9 showed worse CSM for LTA relative to PN. However, their historic nature represents a limitation; the most recent included patients diagnosed from 2004 to 2013 12 . Moreover, with the exception of SEER-Medicare studies 10,11 that exclusively focused on patients older than 65 years, no stratification was performed according to age.…”
Section: Introductionmentioning
confidence: 86%
“…Three recent studies used the National Cancer Institute's SEER cancer registry to ascertain survival outcomes of ablation compared to surgical techniques for small renal masses (18)(19)(20).…”
Section: Management Of T1a Renal Masses Cohort and Registry-based Stumentioning
confidence: 99%
“…Zhou et al (18) used the SEER database in a study comparing ablation (either cryoablation or thermal ablation) to PN in patients from 2004 to 2013. In the propensity-matched cohort, the PN group had significantly increased overall 5-year survival compared to the ablation group (91.0% vs 86.3%; hazard ratio [HR] ¼ 1.442; 95% confidence interval [CI], 1.005-2.068; P ¼ .0457).…”
Section: Management Of T1a Renal Masses Cohort and Registry-based Stumentioning
confidence: 99%